Evaluation of upper arm muscle and fat area of children and adolescents from Ankara, Turkey - Yavuz, Cansev Meşe; Özer, Başak Koca (Anthropological Review, 2020)
Arm anthropometry is a commonly used method for determining the nutritional status of children and adolescents. The purpose of the study is to evaluate the arm anthropometry of 1484 children and adolescents (760 boys and 724 girls) aged between 6–17 years. The sample groups are selected who are living in Ankara to establish local reference values. In order to determine upper Arm Muscle Area (AMA) and upper Arm Fat Area (AFA), height, weight, upper arm circumference and triceps skinfold thickness measurements were taken in accordance with International Biological Program (IBP) protocols. Smoothed percentiles of AMA and AFA were obtained. Body mass index was calculated with weight and height measurements (kg/m2). Fat mass (FM) and fat free mass (FFM) were measured using bio-impedance analyzer. According to the obtained results, arm muscle area values were higher in boys and arm fat area was higher in girls. In addition, sex difference in these variables increased with age. There was a high positive correlation between body mass index (BMI) and AMA, AFA. It has been found that there is a difference in AMA and AFA values for Ankara children compared to previous studies in Turkey.